GROUP GUIDANCE USING SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TO REDUCE STUDENT’S CAREER ANXIETY - Ramanda, Peni; Khairat, Imalatul; Yusof, Hapsah Md; Fitria, Elsa; Rifa’i, Hamzah (Jurusan Bimbingan dan Konseling, 2025)
This study aims to examine: (1) the implementation of group guidance services using the SEFT (Spiritual Emotional Freedom Technique); (2) the career anxiety condition among students at the Faculty of Tarbiyah and Teacher Training (FTK), UIN Banten; and (3) the effectiveness of group guidance with SEFT technique in reducing students' career anxiety. The research method employed a quantitative experimental approach using a One-Group Pretest-Posttest design. Seven students were selected as samples through purposive sampling and assigned as members of the group guidance session (experimental group). Data collection involved administering a pretest and posttest using the Student Career Anxiety Scale (SCAS), developed based on Greenberger & Padesky's theory. The data were analyzed using the Wilcoxon signed-rank test. The results revealed that: (1) group guidance was conducted over five sessions following the stages of group development forming, transition, working, and closing—with each session focusing on one career-related topic; the SEFT technique was implemented at the beginning of the closing stage; (2) career anxiety among FTK UIN Banten students showed a progressive decline in average scores: 62.43 (pretest), 60.57 (after first treatment), 59.43 (after second treatment), 58.29 (after third treatment), 52.57 (after fourth treatment), and 50.43 (after final treatment); and (3) the group guidance service using the SEFT technique was effective in reducing students’ career anxiety, with a statistically significant value of 0.018 (< 0.05). These findings highlight the potential for developing a career guidance model that integrates both spiritual and emotional dimensions. Keywords: Group Guidance, SEFT Technique, Career Anxiety